Navigating the Entrepreneurial Landscape: A Qualitative Exploration of SME Success Factors - Jannah, Miftakhul; Susyanti, Jeni; Farida, Eka (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to comprehensively analyze the critical success factors influencing small and medium enterprises (SMEs) through a qualitative exploration of existing literature and empirical studies. The study investigates key determinants such as access to finance, market conditions, regulatory environment, technological advancements, entrepreneurial capabilities, innovation, strategic planning, adaptability, and leadership qualities. Using a systematic literature review methodology, various sources including academic journals, industry reports, and case studies were analyzed to understand the interplay and relative importance of these factors across different contexts. The findings reveal that access to finance significantly impacts SME growth and innovation, emphasizing the role of supportive financial frameworks. Moreover, market orientation and adaptive capabilities emerge as crucial for SMEs to navigate competitive landscapes and capitalize on market opportunities. Innovation and strategic planning are identified as drivers of SME competitiveness, facilitating differentiation and sustainable growth. Leadership qualities, particularly transformational leadership, are shown to enhance organizational performance and foster innovation cultures within SMEs. The study contributes a nuanced understanding of SME success factors, offering insights for policymakers and entrepreneurs to develop targeted strategies that promote SME resilience and sustainability in dynamic global markets.